1-methyl cyclopropene (1-MCP) for quality preservation of fresh fruits and vegetables - Lata, Deep; Kuchi, Venkata Satish; Nayik, Gulzar Ahmad (Journal of Postharvest Technology, 2017)
The use of 1-methyl cyclopropene (1-MCP) is a commercial strategy commonly used for handling of several fruits and vegetables, as pre and  postharvest application extends their shelf life. Ethylene promotes rapid ripening, softening and early senescence of fruits and vegetables. It  binds with receptors present in fruit tissues and elicits functions.1-MCP binds with ethylene receptors and blocks ethylene mediated responses  in fruits and vegetables. Its efficacy depends on various factors such as cultivar, harvesting and maturity stage, concentration, exposure  duration, time, etc. It delays many physiological disorders and chilling injury development in several commodities. This review explores the  role of 1-MCP for quality preservation of fruits and vegetables.
Keywords: 1-MCP; ethylene action; ethylene management; shelf life; senescence